Effects of high pressure homogenization on the solubility, foaming, and gel properties of soy 11S globulin. (March 2022) - Kang, Zhuang-Li; Bai, Rong; Lu, Fei; Zhang, Tao; Gao, Zai-Shang; Zhao, Sheng-Ming; Zhu, Ming-Ming; Ma, Han-Jun
Abstract: The effects of different homogenization pressure levels on the solubility, particle size, surface hydrophobicity, free sulfhydryl content, surface tension, water distribution and mobility, rheological, foaming and gel properties of soy 11S globulin were investigated in this study. High-pressure homogenization treatment (50–150 MPa) significantly increased the magnitude of protein zeta potential, solubility, while reduced the particle size, which increased surface hydrophobicity, and exposure to free sulfhydryl and disulfide bonds, as well as surface tension, foaming capacity and stability, elasticity index, macroviscosity index, initial apparent viscosity and shear stress. On the other hand, excessive pressure treatment at 150 MPa caused solubility, surface hydrophobicity, exposure to free sulfhydryl, the elasticity index, macroviscosity index, initial apparent viscosity and shear stress to decrease. The gel strength and water immobilization also increased, whereas the mobility of the water was low. Overall, our results show that high-pressure homogenization improves the physicochemical, foaming and gel properties of 11S globulin. Graphical abstract: Image 1 Highlights: HPH decreased particle size, increased foaming capacity and stability, initial apparent viscosity and shear stress. HPH exposed more surface hydrophobicity, free sulfhydryl and disulfide bonds. Over 150 MPa, solubility, surface hydrophobicity, free sulfhydryl were lowered. HPH could improve the physicochemical, foaming and gel properties.